Relationship between Traders Behaviour in Applying Health Protocols to Covid-19 Incidents in the New Normal Era at Batam's Botania Market - Herdianti; Vika Adasari Yulita; Bahzomi Fuadi (Universitas Mandala Waluya, 2022)
The implementation of health protocols is an effort made to ensure that individuals and communities remain healthy and protected from Covid-19. In the working area of ​​the Batam City Health Center, the highest number of Covid-19 cases is in the first place. This study aims to determine the relationship between the behaviour of market traders and the new normal era of Covid-19 cases at the Batam Botania Market. This research is a quantitative analytic observational study with a cross-sectional design. The population in this study amounted to 57 respondents using the total sampling technique. The instrument used in this study was a questionnaire. The results showed that there was a relationship between attitudes (p-value = 0.006 <a 0.05) and actions (p-value = 0.053 <a 0.05) and there was no relationship between knowledge (p-value = 1.000 >a 0, 05) on the Covid-19 case at the Batam Botania Market. Suggestions for the community to further improve behaviour in the main family environment, in order to increase efforts to prevent transmission of the Covid-19 virus during the current pandemic. The conclusion of the study is that there is no relationship between knowledge and action in the application of health protocols during the Covid-19 period. There is a relationship between the attitude toward applying health protocols to the incidence of Covid-19. Suggestions for the public to apply health protocols during the Covid-19 period to avoid widespread spread.